2017
DOI: 10.3390/ijerph15010024
|View full text |Cite
|
Sign up to set email alerts
|

Concept of Aided Phytostabilization of Contaminated Soils in Postindustrial Areas

Abstract: The experiment was carried out in order to evaluate the effects of trace element immobilizing soil amendments, i.e., chalcedonite, dolomite, halloysite, and diatomite on the chemical characteristics of soil contaminated with Cr and the uptake of metals by plants. The study utilized analysis of variance (ANOVA), principal component analysis (PCA) and Factor Analysis (FA). The content of trace elements in plants, pseudo-total and extracted by 0.01 M CaCl2, were determined using the method of spectrophotometry. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 47 publications
(52 reference statements)
2
16
0
10
Order By: Relevance
“…In this study, the high amount of increase in pH of soil was looked after 8 week with application of 5% diatomite in soil ( Table 2). The results of this study are confirmed with the other researches such as Radziemska et al (2018), Ye et al (2015) and Radziemska et al (2017), who observed that the application of natural and modified diatomite intensified the value of pH in soil and consequently decreased labile forms of heavy metals.…”
Section: And Pb Fractionssupporting
confidence: 90%
“…In this study, the high amount of increase in pH of soil was looked after 8 week with application of 5% diatomite in soil ( Table 2). The results of this study are confirmed with the other researches such as Radziemska et al (2018), Ye et al (2015) and Radziemska et al (2017), who observed that the application of natural and modified diatomite intensified the value of pH in soil and consequently decreased labile forms of heavy metals.…”
Section: And Pb Fractionssupporting
confidence: 90%
“…Based on the use of plants and their associated microorganisms, phytotechnologies are considered as environmental-friendly, cost-effective, and benefit from a high public acceptance [ 1 , 3 , 4 ]. One of the main strategies, referred to as phytostabilisation, resides in the immobilisation of the pollutants in the plant rhizosphere to reduce their bioavailability and alleviate wind and water erosion phenomena [ 5 , 6 ]. However, increased concentrations of TE may impair plant growth and weaken the success of the method [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result may be due to several parameters. Firstly, in this study, improvement of soil physicochemical properties was only related to the action of engineering native plant species and associated microorganisms, contrary to most phytostabilization studies using amendments (Rizzi et al, 2004;Radziemska et al, 2018).…”
Section: Evaluation Of Phytostabilization Success After Three Yearsmentioning
confidence: 77%
“…Thus, at the ecological restoration plots, improving the soil quality exclusively by plants and their impact on MM retention may take more time than when using amendments which hasten MM toxicity reduction and limit their bioavailability by adsorption and complexation processes (Rizzi et al, 2004;Mendez and Maier, 2008;Epelde et al, 2009;Radziemska et al, 2018). Then, MM immobilization by microorganisms by biosorption, bioaccumulation and transformation (Adriano et al, 2004;Khan, 2005;Ma et al, 2011) is limited by low biomass and microbial activities at the ecological restoration plots.…”
Section: Evaluation Of Phytostabilization Success After Three Yearsmentioning
confidence: 99%